PENGARUH KOMPETENSI DAN INDEPENDENSI TERHADAP KUALITAS AUDIT APARAT INSPEKTORAT DALAM PENGAWASAN KEUANGAN DAERAH DI PROVINSI SULAWESI UTARA - Sumiok, Cristofer; Pontoh, Winston (Universitas Sam Ratulangi, 2013)
In presenting a good financial governance, the Local Government must be able to present the financial statements in accordance with the local government Permendagri 13 of 2006 and the Government Accounting Standards ( SAP ) . To obtain these results certainly not out of the factors that support the implementation of the financial statements as rules / regulat ions, education, experience, commitment to employees, and supporting tools that support the creation of the ability of the involved parties in the preparation of the financial statements of Local Government.The purpose of this research aim to know the influence of competence and independence with quality audit regional inspectorate officers as financial control in the province of North Sulawesi.The Data was collected by survey with questionnaire contain list of question that have to fill by internal auditors in inspectorate as respondent. Technique data analyzing to the test the hypothesis by multiple linear regression using SPSS Ver 19.0.The result by using F-test shows that competence ( X1 ) and independence ( X2) on the test result indicate that the variabel F competence ( X1 ) and independence ( X2 ) has significant correlation with audit quality regional inspectorate officers in the province of north Sulawesi. the result of F test shows that Fhit = 6,016 and Ftab with confidence level 95% df1 ( 2 ) and df2 ( 46 ) is 2,81 at level significance 0,002 < α: 5% ( 0,05) it means Ha could accepted the result of t test show that pnly competence variables that has influence with audit quality in regional inspectorate officers in the province of northSulawesi. t hit, shows 3,864 > t2,014 at level significance 0,000 < 0,05 Independence variable shows thit 0,986 < ttabtab2,014 at level significance 0,329 > 0,05 it means that independent variable didn’t influence with audit quality regional inspectorate officer in the province of north Sulawesi.Key Words : competence, independence